Notch signaling pathway involved in Echinococcus granulosus infection regulates dendritic cell development and differentiation - Wang, Mingxia; Shang, Zailing; Qiao, Fei; Hei, Junhu; Ma, Xueling; Wang, Yana (Frontiers in Cellular and Infection Microbiology, 2023)
The Notch signaling pathway is involved in the development of many diseases; it regulates the development of dendritic cells (DCs), and affects the immune response of DC-mediated T cells. We previously found that ferritin and malate dehydrogenase (mMDH) in Echinococcus granulosus (E.granulosus) induced different immune responses through sensitized DCs. To clarify whether the Notch signaling pathway is involved in this process, we used the Notch signaling pathway inhibitor [N-[3,5-difluorophenace-tyl]-L-alanyl]-S-phenylglycinet-butyl ester (DAPT) or activator Jagged1 to construct in vitro cell models with blocked or activated Notch signaling respectively. We analyzed the effect of Notch signaling on the development and differentiation of DCs by detecting their morphology, migration function, capacity to promote T cell proliferation, and cytokine secretion. We observed the changes in DC response to E. granulosus antigens and the mediated immune response. We showed that DAPT inhibited the development and maturation of DCs, which were in a non-responsive or incompetent state, reduced the sensitization of DCs to Eg.ferritin, weakened the migration ability of DCs, disrupted their ability to mediate T-cell proliferation, reduced DC expression of MHCII, CD80, CD60, and CD40 co-stimulatory molecules, prevented the secretion of cytokines and attenuated the expression of Notch1, Notch2, Notch3 receptors, Jagged1, Delta-like 4 (Delta4), and Hes1. Following Jagged1 addition, the function of DCs was restored to some extent, and the expression of Notch1, Delta4 and Hes1 was activated in response to the stimulation of Eg.ferritin. However, Eg.mMDH stimulated DCs to produce an immune response showing weak interference by DAPT and Jagged1. This suggests that the Notch signaling pathway is involved in the Eg.ferritin-sensitized DC-mediated immune response, which may become a new target for treating E. granulosus infection.